The neurophysiological approach to misophonia: Theory and treatment - Jastreboff, Pawel J.; Jastreboff, Margaret M. (Frontiers in Neuroscience, 2023)
Clinical observations of hundreds of patients who exhibited decreased tolerance to sound showed that many of them could not be diagnosed as having hyperacusis when negative reactions to a sound depend only on its physical characteristics. In the majority of these patients, the physical characteristics of bothersome sounds were secondary, and patients were able to tolerate other sounds with levels higher than sounds bothersome for them. The dominant feature determining the presence and strength of negative reactions are specific to a given patient patterns and meaning of bothersome sounds. Moreover, negative reactions frequently depend on the situation in which the offensive sound is presented or by whom it is produced. Importantly, physiological and emotional reactions to bothersome sounds are very similar (even identical) for both hyperacusis and misophonia, so reactions cannot be used to diagnose and differentiate them. To label this previously non-reported phenomenon, we coined the term misophonia in 2001. Incorporating clinical observations into the framework of knowledge of brain functions allowed us to propose a neurophysiological model for misophonia. Observation that physical characterization of misophonic triggers were secondary and frequently irrelevant suggested that the auditory pathways are working as in people without misophonia. Descriptions of negative reactions indicated that the limbic and sympathetic part of the autonomic nervous systems are involved, but without manifestations of general malfunction of these systems. Misophonic patients could not control internal emotional reactions (even when fully realizing that these reactions are disproportionate to benign sounds evoking them) suggesting that subconscious, conditioned reflexes linking the auditory system with other systems in the brain are the core mechanisms of misophonia. Consequently, the strength of functional connections between various systems in the brain plays a dominant role in misophonia, and the functional properties of the individual systems may be perfectly within the norms. Based on the postulated model, we proposed a treatment for misophonia focused on the extinction of conditioned reflexes linking the auditory system with other systems in the brain. Treatment consists of specific counseling and sound therapy. It has been used for over 20 years with a published success rate of 83%.